A teaching to come: perspectives in fabulation (Palíndromo, 2023)
How to build a teaching path in a narrative in which fabulation and literature break through writing, crossing not only the text, but also the experiences in contemporary art-education? Even if the search for answers is what moves a research, in this text, it moves the desire to fable in the path between being and feeling teacher. This is composed do not seek to establish truths, nor to name events, stories, teachers, and students. However, they aim to create a teaching in Visual Arts always to come. In this relationship, being a teacher marks a state in suspension, in a paused movement, while feeling a teacher aligned a movement, breaking with the linearity of training and deriving in narrative possibilities. Such things are explored with the sharing of narratives by some teachers in the State of Santa Catarina. Although located in a wide geographic location, these educators make it possible to create becomings close to the teaching practice in a classroom, whether here or there. Fabulating a teaching in arts consists of narratives, singular and collective, as it speaks to a people to come, in a minor language, always in motion. In this conception, the teachers’ speeches shared in this text do not gain a name or surname, but a space to talk about the reality of teaching, in a kind of foreign language, in such a way that it can reach the fabulation in the interstices of language.
Keywords: Fabulation; Teacher training; Being/feeling a teacher; Visual Arts